Ki Hajar Dewantoro's Tri Nga Concept in Learning the Macapat Song to Aba Ngabean 2 Kindergarten Children - Ad Dieni Maulana Rizka; Joko pamungkas; Septika Cahya Rahmawati; Erina Putri Anggraeni (PT. Publikasiku Academic Solution, 2022)
Background: Good citizens are people who want to continue the heritage culture of their ancestors. Cultural values ??are very useful for life in the future. Aim: This study aims to find out how the implementation of the macapat song through the Tri Nga Ki Hajar Dewantara approach for early childhood in TK ABA Ngabean 2. Method: The implementation method used is a descriptive qualitative approach with data collection techniques through observation, documentation, and interviews. Findings: An early childhood education institution in Kapanewon Tempel, Sleman Regency, there is one school that received the title of an innovation school in Sleman and is a core PAUD and Aisyiyah Pilot Kindergarten in Kapanewon.